2017
DOI: 10.1186/s12263-017-0552-8
|View full text |Cite
|
Sign up to set email alerts
|

A porcine gluteus medius muscle genome-wide transcriptome analysis: dietary effects of omega-6 and omega-3 fatty acids on biological mechanisms

Abstract: Background: The level of omega-6 and omega-3 polyunsaturated fatty acids can affect many cellular systems and function via nuclear receptors or the bioactive lipid regulation of gene expression. The objective of this study was to investigate changes in the muscle transcriptome and the biological functions regulated by increased consumption of omega-3 and omega-6 fatty acids in the pig gluteus medius muscle. Results: The transcriptome of the gluteus medius muscle was studied for pigs subjected to either a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Aim of the presented study was to investigate the liver transcriptome and to explore the genetic variability in terms of SNPs/SNVs in the Polish Landrace pigs fed with PUFAs diets. Our results provide novel cSNP transcriptomic data (https://www.ncbi.nlm.nih.gov/sra) of Polish Landrace breed to explain the regulatory mechanisms of the liver tissue's biological response to increased concentration of PUFAs diets [22]. Related studies showed that consumption of PUFAs and other fatty acids diets were genetically regulated the growth performance and immune system in pigs [23].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Aim of the presented study was to investigate the liver transcriptome and to explore the genetic variability in terms of SNPs/SNVs in the Polish Landrace pigs fed with PUFAs diets. Our results provide novel cSNP transcriptomic data (https://www.ncbi.nlm.nih.gov/sra) of Polish Landrace breed to explain the regulatory mechanisms of the liver tissue's biological response to increased concentration of PUFAs diets [22]. Related studies showed that consumption of PUFAs and other fatty acids diets were genetically regulated the growth performance and immune system in pigs [23].…”
Section: Discussionmentioning
confidence: 71%
“…Research materials: The liver tissues samples of Polish Landrace pigs for RNA-seq based NGS experiment were selected on the basis of fatty acid profiles in order to compare the liver transcriptomes characterized by low (control groups) and high (PUFAs enriched diet groups) omega-6/ omega-3 fatty acids ratio in Polish Landrace pigs. The threshold value of < 7 for low and > 7 for high omega-6/omega-3 fatty acids ratio was used in accordance to previous study [22]. After slaughtering, the liver tissues were collected at the Institute IGHZ, Jastrzębiec and were frozen in liquid nitrogen and stored at − 80°C for further RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Our results provide novel cSNP transcriptomic data (https://www. ncbi.nlm.nih.gov/sra) of Polish Landrace breed to explain the regulatory mechanisms of the muscle tissue's biological response to increased concentration of omega-6 and omega-3 fatty acids (PUFAs) diets [22]. Recent studies have reported that consumption of PUFAs and other fatty acids diets were genetically regulated the growth performance and immune system in pigs [23].…”
Section: Discussionmentioning
confidence: 99%
“…The gluteus medius muscle samples of Polish Landrace pigs for RNA-seq based NGS experiment were selected based on fatty acid profiles in order to compare muscle transcriptomes characterized by low (control groups) and high (PUFAs enriched diet groups) omega-6/omega-3 fatty acids ratio in Polish Landrace pigs. The threshold value of < 7 for low and > 7 for high omega-6/omega-3 fatty acids ratio was used in this study [22]. After slaughtering the gluteus medius muscle tissues were collected at the Institute IGHZ, Jastrzębiec and were frozen in liquid nitrogen and stored at − 80 °C for further RNA extraction.…”
Section: Animalsmentioning
confidence: 99%
“…Another suggested mechanism is that through its ability to increase muscle cell membrane lipid content/composition and fluidity, LCn-3PUFAs supplementation may modulate key substrates along the anabolic signaling cascades such as the activating protein kinase C (PKC) pathway, which leads to increased translational activity and protein synthesis (Smith et al, 2011b). More importantly, several studies in human and other animal models (Castillero et al, 2009;Ogluszka et al, 2017;Yoshino et al, 2016) support that LCn-3PUFAs supplementation leads to transcriptional regulation of skeletal muscle metabolism thus contributing to the aforementioned mechanisms. For instance, Yoshino et al (2016) found that the beneficial effects of LCn-3PUFAs on muscle mass, strength, and function in older adults may be in part transcriptionally regulated and involve gene set pathways related to mitochondrial function, structural support, anabolic signaling, and both calpainand ubiquitin-mediated proteolysis.…”
Section: Skeletal Muscle Condition Is Critical To Survival In Variomentioning
confidence: 99%